Challenges And Methods in Laboratory Testing of Biofilm-Forming Pathogens in Chronic Infections - Khan, Muhammad Naeem; Usmani, Abeeha; Hamad, Maryam AbuBaker; Farrukh Alavi, Amina; Shelke, Girish Suresh (Journal of Neonatal Surgery, 2025)
Background: Bacterial biofilms play a significant role in chronic infections, as they contribute to the persistence of pathogenic bacteria by protecting them from both host immune responses and antimicrobial treatments. This study aims to examine the relationship between bacterial biofilm formation and healthcare satisfaction among patients with chronic illnesses, with a focus on the influence of demographic and lifestyle factors. Objectives: The primary objectives of this research are to investigate the prevalence of bacterial biofilms in chronic infections, analyze the impact of patient demographics (age, years of illness) on healthcare satisfaction, and evaluate the role of lifestyle factors, particularly physical activity, in improving healthcare outcomes. Methods: A cross-sectional design was employed, where 250 participants diagnosed with chronic illnesses were surveyed to collect data on demographics, healthcare satisfaction, physical activity, and overall lifestyle. Laboratory tests were conducted to measure bacterial biofilm formation, and several statistical tests, including normality tests (Shapiro-Wilk), correlation analysis, Cronbach’s alpha for reliability, and regression analysis, were performed to analyze the data. Results: The Shapiro-Wilk test indicated that none of the variables followed a normal distribution. Cronbach's alpha showed a moderate internal consistency among healthcare-related variables. Correlation analysis revealed strong negative correlations between healthcare satisfaction and both age and years of illness, while physical activity was positively correlated with healthcare satisfaction. The regression analysis confirmed that physical activity and lifestyle factors significantly predict healthcare satisfaction. Conclusion: The study demonstrates that both demographic factors (age, years of illness) and lifestyle interventions (physical activity) significantly impact healthcare satisfaction in chronic illness patients. Physical activity emerged as a crucial factor in enhancing patient satisfaction. Future research should explore the role of other lifestyle interventions and refine the tools used to measure healthcare satisfaction in chronic disease management.